Capital Structure, Accounting Conservatism, Agency Cost, dan Firm Value - Vika Aprianti; Khomsiyah Khomsiyah (Politeknik Ganesha Medan, 2022)
The purpose of this research is to evaluate how capital structure, accounting conservatism, and agency cost impact firm value. The financial reports companies listed on the IDX in 2019–2021 are data utilized in this analysis. The website of the Indonesian Stock Exchange (IDX) supplied the information for this research. There are 671 companies listed in 2019, 716 in 2020, and 769 in 2021. The samples in this research are non-cylicals consumer sector companies. There are 87 companies which was fit the criteria. The study aimed to investigate whether capital structure, accounting conservatism, and agency cost had an effect on firm value. Consequently, there was no effect of the company's capital structure on firm value. This indicates that shareholders are not too focused on capital structure to assess a company. However, companies that had high agency costs followed by good management. Thus, firm value was also high because it could be taken into consideration by shareholders to oversee management actions to support a better firm value. Then, accounting conservatism which showed caution over uncertainty in maintaining the quality of reported earnings. Accounting conservatism has a negative effect on firm value, this indicates that shareholders prefer companies that do not carry out accounting conservatism so that there is no early recognition of losses and company profits remain high.